PENGARUH PENGGUNAAN METODE EXPERIENTIAL LEARNING DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK KELAS V SDN GARATENGAH - Endang Paramita; Nana Sutarna (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
ABSTRACT The learning process in the 21st century must provide students with 4C skills, including critical thinking skills. Contrary to the fact that students are still lacking in this ability. To achieve this goal, repeated activities are needed, and the application of the Experiential Learning method will support teachers in developing and triggering the improvement of critical thinking skills in students. This study applies a quantitative approach in a quasi-experimental design, with a population of fifth-grade students from SDN Garatengah and SDN 3 Jalaksana and uses a purposive sampling technique. The data analysis methods applied in this study include validity tests, reliability tests, discrimination power tests, question difficulty tests, normality tests, homogeneity tests, N-Gain tests, and hypothesis testing. The results of the independent sample t-test show a Sig. (2-tailed) value with the assumption of equal variance of 0.004. Therefore, it can be concluded that the Sig. value. (2-tailed) 0.004 < 0.05 indicates the effect of implementing the Experiential Learning method in improving the critical thinking skills of fifth-grade students in science learning in elementary schools. The N-Gain test result was 60.68421 or 60%, indicating that the Experiential Learning method had a significant effect in improving students' critical thinking skills.